Effects of 2 years of caloric restriction on oxidative status assessed by urinary F2‐isoprostanes: The CALERIE 2 randomized clinical trial - Il'yasova, Dora (Aging Cell, 2018)
Calorie restriction (CR) without malnutrition slows aging in animal models. Oxidative stress reduction was proposed to mediate CR effects. CR effect on urinary F2‐isoprostanes, validated oxidative stress markers, was assessed in CALERIE, a two‐year randomized controlled trial. Healthy volunteers (n = 218) were randomized to prescribed 25% CR (n = 143) or ad libitum control (AL, n = 75) stratifying the randomization schedule by site, sex, and BMI. F2‐isoprostanes were quantified using LC‐MS/MS in morning, fasted urine specimens at baseline, at 12 and 24 months. The primary measure of oxidative status was creatinine‐adjusted 2,3‐dinor‐iPF(2α)‐III concentration, additional measured included iPF(2α)‐III, iPF2a‐VI, and 8,12‐iso‐iPF2a‐VI. Intention‐to‐treat analyses assessed change in 2,3‐dinor‐iPF(2α)‐III using mixed models assessing treatment, time, and treatment‐by‐time interaction effects, adjusted for blocking variables and baseline F2‐isoprostane value. Exploratory analyses examined changes in iPF(2α)‐III, iPF(2α)‐VI, and 8,12‐iso‐iPF(2α)‐VI. A factor analysis used aggregate information on F2‐isoprostane values. In CR group, 2,3‐dinor‐iPF(2α)‐III concentrations were reduced from baseline by 17% and 13% at 12 and 24 months, respectively; these changes were significantly different from AL group (p < .01). CR reduced iPF(2α)‐III concentrations by 20% and 27% at 12 and 24 months, respectively (p < .05). The effects were weaker on the VI‐species. CR caused statistically significant reduction in isoprostane factor at both time points, and mean (se) changes were −0.36 (0.06) and −0.31 (0.06). No significant changes in isoprostane factor were at either time point in AL group (p < .01 between‐group difference). We conclude that two‐year CR intervention in healthy, nonobese men and women reduced whole body oxidative stress as assessed by urinary concentrations of F2‐isoprostanes.